Machining distortion in the milling of multi-frame components. (August 2021) - Wang, S.Q.; He, C.L.; Cao, Z.M.
Abstract: Machining distortion is extensively observed in the milling of multi-frame components due to residual stress and low rigidity. Therefore, it is critical to accurately predict the distortion and develop corresponding reduction technology in the milling of multi-frame components. In this paper, a novel analytical model to predict the machining distortion of multi-frame components was established based on the energy method. The influence of bulk residual stress inner the material, machining induced residual stress and the characteristics of workpiece structure were taken into account in this theoretical model. Milling experiments were performed on two classical multi-frame components including rib, web and hole to verify the proposed model. Measurement results of 3D and 2D distortions of the components were compared with prediction results. Fine consistency between the two results demonstrated the accuracy of the established theoretical model. According to the theoretical results, a new parameter with general consideration of the influence of bending curvature in x - and y -direction was formulated as distortion coefficient and further applied to adjust the processing parameters to reduce the distortion. Furthermore, the corn starch suspension with shear thickening property was also successively employed to reduce the machining distortion at the mean time. Milling experiment results successfully proved the effectiveness of the proposed methods in this work, and the machining distortion can be reduced nearly by 20%.